1,3-Dipolar Cycloaddition Reactions of 2-Arylmethylidentiazolo[3,2-a]pyrimidines with Azomethinylides: Studying the Supramolecular Organization of Products in the Crystalline Phase - Anna Nefedova; Darya Tretyakova; Dilyara Mingazhetdinova; Artem Agarkov; Alexander Ovsyannikov; Igor Litvinov; Svetlana Solovieva; Igor Antipin (Chemistry Proceedings, 2024)
The [3+2]-cycloaddition of azomethinylides formed in situ to dipolarophiles is a promising approach for the synthesis of dispyroderivatives of oxindole and acenaphthenedione. In the course of our studies, it was shown that the cycloaddition of azomethinylides occurs specifically through the exocyclic double C=C bond resulting in the formation of a new pyrrolidine cycle as part of the molecule and, consequently, a dispyroheterocycle. This work is devoted to the synthesis and structural analysis of dispyrothiazolo[3,2-a]pyrimidine in the crystalline phase.